2020
DOI: 10.1038/s41420-020-00329-4
|View full text |Cite|
|
Sign up to set email alerts
|

Gut microbiota patterns associated with somatostatin in patients undergoing pancreaticoduodenectomy: a prospective study

Abstract: Postoperative pancreatic fistula (POPF) is a common and dreaded complication after pancreaticoduodenectomy (PD). The gut microbiota has been considered as an crucial mediator of postoperative complications, however, the precise roles of gut microbiota in POPF are unclear. A prospective study was developed to explore the effects of somatostatin on gut microbiota and we aim to identify the microbial alterations in the process of POPF. A total of 45 patients were randomly divided into PD group or additional somat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…3B , Kruskal–Wallis test, p = 2.17 × 10 −64 , E 2 = 0.102). Considering specifically the top 20 drugs (in terms of their mean impact on microbial taxa) that have not been screened in the original database, we found several compounds with reported in vivo anti-commensal activity such as the immunosuppressants Sirolimus 29 and Tacrolimus 30 and the antineoplastic agents Somatostatin 31 and Eribulin 32 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…3B , Kruskal–Wallis test, p = 2.17 × 10 −64 , E 2 = 0.102). Considering specifically the top 20 drugs (in terms of their mean impact on microbial taxa) that have not been screened in the original database, we found several compounds with reported in vivo anti-commensal activity such as the immunosuppressants Sirolimus 29 and Tacrolimus 30 and the antineoplastic agents Somatostatin 31 and Eribulin 32 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, medications affecting the sensory, genitourinary, and respiratory systems show the lowest average activity (Figure 3B). Considering specifically the top 20 drugs (in term of their mean impact on microbial taxa) that have not been screened in the original database, we found several compounds with reported in-vivo anti-commensal activity such as, the immunosuppressants Sirolimus 29 and Tacrolimus 30 and the antineoplastic agents’ Somatostatin 31 and Eribulin 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, LEfSe analysis ( Li et al, 2020 ) identified 42 signature bacterial taxa that were differentially altered, with an LDA score > 2, showing that there was a significant structural difference among the four groups ( Figure 3C ), in which 13 bacterial species were identified as key discriminants. All these results demonstrated that repeated stress-related diarrhea may be a key modulator of the microbiota composition, and the key bacteria may be able to identify repeated stress-related diarrhea disease.…”
Section: Resultsmentioning
confidence: 99%